Developing and validating instruments for measuring critical thinking and clinical decision-making constructs for nurses in Malaysia - Zainal @ Muhamad, Nur Hidayah (2020)
Critical Thinking (CT) and Clinical Decision-making (CDM) are two important skills for nurses to provide a quality nursing care. Hence, the aims of this research were to: (i) develop a questionnaire on Critical Thinking and Clinical Decision- Making Scale (CT & CDMS); (ii) determine the validation study of CT & CDMS. The initial version of CT & CDMS was developed based on two models: 4-Circle Critical Thinking Model and Conflict-Theory Model of Decision-making. During the pre-testing stage, the nursing expert professionals were involved to obtain the content validity and the language experts were involved in consensus for face validity. Next, the instrument was distributed to 16 nurses, in order to gather their comments, and check the consistency in their responses. Subsequently, the researcher distributed the questionnaire to gather data from 200 respondents. Using data from pilot study, the researcher performed the Exploratory Factor Analysis (EFA) through IBM-SPSS 24.0 in order to assess the usefulness of every item. Based on the results from EFA, the researcher rearranged the questionnaire accordingly and performed field study survey where another 200 respondents were sampled. Using the data from field study, the researcher performed the Confirmatory Factor Analysis (CFA) procedure through IBM-SPSS-AMOS 23.0 in order to validate the instrument for construct validity, convergent validity, discriminant validity and composite reliability. Overall, judgement from the expert showed that 36 items from two constructs with CVR value of 1.00. However, after refinement, the instrument had 38 items retained with the mean I-CVI level for the relevance, clarity and simplicity scale for CT construct was 1.00, the S-CVI/UA was 1.00 and mean expert proportion was 1.00. However, the mean I-CVI level for the ambiguity scale for CT construct was 0.99, the S-CVI/UA was 0.95 and mean expert proportion was 0.99. Meanwhile, the mean I-CVI level for the relevance, clarity, simplicity and ambiguity scale for CDM construct was 0.99, the S-CVI/UA was 0.95 and mean expert proportion was 0.99. In addition, the face validity showed good comprehensibility and feasibility. The EFA procedure has reduced the items from 38 to 21. Meanwhile, the CFA procedure has confirmed the construct validity through the fitness indexes namely Chi square/df (2.111), CFI (0.965), TLI (0.951) and RMSEA (0.075) for the CT construct while Chi square/df (1.992), CFI (0.980), TLI (0.972) and RMSEA (0.071) for the CDM construct. Overall CT & CDM produced very good internal consistency with Cronbach’s alpha value of 0.865 and 0.891 for factor 1 and factor 2 for CT and 0.945 and 0.841 for factor 1 and factor 2 for CDM construct respectively. The convergent validity for the construct was achieved through Average Variance Extracted (AVE) value of 0.834 for CT and 0.907 for CDM. Four factors extracted by EFA consist of 21 items were named as Critical Characteristic, Critical Knowledge, Decision Abilities and Decision Accuracy. Thus, the CT & CDMS was concluded to be a reliable and validated instrument in measuring the level of critical thinking and clinical decision-making of nurses in clinical settings.